Principal Leadership Management Through The Implementation of Four Deep Learning Frameworks to Increase the Motivation of Elementary School Teachers (Case Study of SDN Ciwangi Bungursari Purwakarta) - Suharyanto H Soro; Nana Herdiana Abdul Rahman; Enjang Sarip Hidayat; Rini Rosmiati (Civiliza Publishing, Indonesia., 2026)
The global development of the Industrial Revolution 4.0 and Society 5.0 demands the transformation of education towards Deep Learning to cultivate 21st century skills. The implementation of this concept in elementary schools still focuses on administration, while to drive the education ecosystem depends on the level of teacher motivation which is the spearhead of changes in the quality of learning services. This study aims to describe and analyze the leadership of school principals which includes planning, organizing, implementing, and supervising in implementing four Deep Learning frameworks to increase teacher motivation at SDN Ciwangi. The research method used is qualitative with a case study approach. The data collection method was carried out through non-participatory observation, in-depth interviews, and documentation studies, which were then analyzed using the Miles, Huberman, and Saldana interactive model including data reduction, data presentation, and conclusion drawn. The findings of the study show that (1) Principals have implemented participatory and visionary leadership; (2) The implementation of leadership is transformational through technological example and the creation of a psychologically safe environment, so that teachers dare to innovate without fear of making mistakes. This study concluded that the synergy of leadership management with the four deep learning frameworks succeeded in changing teachers' motivation from mere extrinsic compliance to intrinsic professional commitment (self-efficacy and inner satisfaction).